USE OF ENERGY EFFICIENT TECHNOLOGIES IN VOCATIONAL EDUCATION AND TRAINING INSTITUTIONS (Innovative professional education, 2025)
The ways of studying and implementing energy efficient technologies in vocational (vocational and technical) education institutions through the application of project-based learning methodology are substantiated
Keywords: project-based learning, energy efficiency, ecology, construction industry, environment, skilled worker, vocational education, energy resources, positive motivation